The Strategy of Developing Multicultural Education - Faisal Rahman; Uus Ruswandi; Mohamad Erihadiana (IAIN Ponorogo, 2021)
This article aims to develop a multicultural education strategy in Islamic education. It accommodates the urgency of contemporary needs. It plays a vital role in Islam rahmatan lil 'alamin. In addition, it describes Islamic educators' interpretation transformation using a creative, inclusive, relevant multicultural approach in teaching-learning. This research employed qualitative research. The data were collected through some literature, such as books, articles, and publications. The findings found that the teachers should be equipped with some competencies and skills. They include understanding yourself, developing intercultural/competence, becoming empathic, understanding immediacy, adopting an integrated approach to instruction dan using nondiscriminatory assessment strategies. Developing a multicultural strategy is a step ahead to take Islamic educators' attention. They are also involved in initiating to prevent extremism and strengthen religious moderation. Artikel ini adalah sebuah diskursus pengembangan strategi pendidikan multikultural yang bertujuan menawarkan kepada pendidik agama Islam merespon positif melangkah dan mengakomodasi urgenitas kebutuhan kekinian untuk berperan penting pada sebuah agama yang rahmatan lil ‘alamin. Tulisan ini ingin melihat transformasi interpretasi pelaku pendidik agama Islam dengan pendekatan multikultural yang kreatif, inklusif, relevan dalam pembelajaran dan pengajaran yang bermakna. Penelitian ini merupakan penelitian kualitatif, sedang pengumpulan data dihimpun melalui studi kepustakaan berupa buku-buku, artikel. dan publikasi. Hasil penelitian ini menemukan unsur kompetensi dasar dalam pengembangan penguasaan understanding yourself, developing intercultural/competence, becoming empathic, understanding immediacy, adopting an integrated approach to instruction dan using nondiscriminatory assessment strategies. Pengembangan strategi multikultural ini menjadi pilihan satu langkah maju merangkak untuk mengetuk hati pendidik agama Islam lebih peduli dan terlibat dalam inisiatif pencegahan ekstremisme dan penguatan moderasi beragama